2008
DOI: 10.1371/journal.pone.0003420
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Human MicroRNA and Disease Associations

Abstract: It has been reported that increasingly microRNAs are associated with diseases. However, the patterns among the microRNA-disease associations remain largely unclear. In this study, in order to dissect the patterns of microRNA-disease associations, we performed a comprehensive analysis to the human microRNA-disease association data, which is manually collected from publications. We built a human microRNA associated disease network. Interestingly, microRNAs tend to show similar or different dysfunctional evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
739
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 838 publications
(759 citation statements)
references
References 29 publications
15
739
0
5
Order By: Relevance
“…Moreover, these three miRNAs are all proved to be related to lung cancer (Johnson et al, 2007;Agirre et al, 2008). Our results were corresponding with the former researches, which indicated that the deregulation of miRNAs belonging to the same family may lead to the similar abnormal phonotype (Lu et al, 2008). What's more, these three miRNAs were predicted to be co-expressed according to our synergistic network.…”
Section: Analysis Of Modules In the Mirna Synergistic Networksupporting
confidence: 85%
“…Moreover, these three miRNAs are all proved to be related to lung cancer (Johnson et al, 2007;Agirre et al, 2008). Our results were corresponding with the former researches, which indicated that the deregulation of miRNAs belonging to the same family may lead to the similar abnormal phonotype (Lu et al, 2008). What's more, these three miRNAs were predicted to be co-expressed according to our synergistic network.…”
Section: Analysis Of Modules In the Mirna Synergistic Networksupporting
confidence: 85%
“…Indeed, a recent RWRH-based method has used a semantic similarity network of genes instead of the protein interaction network [34] and shown to outperform the original one [32]. We also note that a disease similarity network can be constructed based on shared disease gene [30], shared pathways [35], shared miRNA [36], shared protein complex [37], shared disease ontology [38] and disease comorbidity [39]. Similarly to RWR, RWRH algorithm has been successfully applied to other problems such as prediction of novel drugtarget interactions [40] as well as novel disease-associated miRNAs [41] and long non-coding RNAs [42].…”
Section: Introductionmentioning
confidence: 92%
“…miRNAs mostly repress translation or induce mRNA degradation of the target genes by complementary interactions (Bartel, 2009; Griffiths‐Jones, Grocock, van Dongen, Bateman, & Enright, 2006). Around 1%–4% genes in the human genome encode for miRNAs and about one‐third of mRNAs are regulated by miRNAs (Lu et al., 2008). It has been well demonstrated that miRNAs play critical roles in many biological processes including cell fate determination, embryonic development, cell proliferation, differentiation, and apoptosis (Esquela‐Kerscher & Slack, 2006).…”
Section: Introductionmentioning
confidence: 99%